A Spectacular Embrace: Dance Dialogues between Cuba and the Soviet Union, 1959–1973. Issue 3 (2nd September 2018) - Schwall, Elizabeth
Abstract: This article examines dance dialogues between Cuba and the Soviet Union during the Cold War, focusing mostly on ballet, with some analysis of folkloric dance. Cuban and Soviet dancers enacted what I call a spectacular embrace, a choreographed relationship that obscured tensions, exaggerated affections, and allowed Cuban dancers to celebrate socialist solidarities while reaffirming national distinctions. This dancing history provides new insights into Cuban-Soviet relations by showing how Cuban dance makers leapt into a spectacular embrace with Soviets when their governments quibbled in the 1960s, and quietly disengaged themselves when their governments became closer in the 1970s.